2013
DOI: 10.4161/psb.26595
|View full text |Cite
|
Sign up to set email alerts
|

Plant as a plenteous reserve of lectin

Abstract: Lectins are clusters of glycoproteins of nonimmune foundation that combine specifically and reversibly to carbohydrates, mainly the sugar moiety of glycoconjugates, resulting in cell agglutination and precipitation of glycoconjugates. They are universally distributed in nature, being established in plants, fungi, viruses, bacteria, crustacea, insects, and animals, but leguminacae plants are rich source of lectins. The present review reveals the structure, biological properties, and application of plant lectins. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 97 publications
1
14
0
1
Order By: Relevance
“…Addition of metal chelating agent like EDTA to E. Lectin and tested for antiviral activity on HSV-I, revealed that some or all antiviral activity of E. Lectin was diminished (disappeared after addition of EDTA) indicating that the lectin was a metaloprotein that needed both Ca +2 and Mn +2 ions for its activity. Similar results ( Figure 6) were obtained by Konozy et al [39]. Also addition of EDTA diminished antiviral activity of E. Lectin when it is applied to vero cells infected with HSV-1.…”
Section: Effect Of Temperature Ph and Denaturantssupporting
confidence: 90%
“…Addition of metal chelating agent like EDTA to E. Lectin and tested for antiviral activity on HSV-I, revealed that some or all antiviral activity of E. Lectin was diminished (disappeared after addition of EDTA) indicating that the lectin was a metaloprotein that needed both Ca +2 and Mn +2 ions for its activity. Similar results ( Figure 6) were obtained by Konozy et al [39]. Also addition of EDTA diminished antiviral activity of E. Lectin when it is applied to vero cells infected with HSV-1.…”
Section: Effect Of Temperature Ph and Denaturantssupporting
confidence: 90%
“…Also, the observed haemagglutination activity of these mucoadhesives could be due to the presence of lectins which is reported to be abundant in plants and its products. These ubiquitous highly specific sugar-binding proteins also have mitogenic, antibacterial, antifungal, antiviral as well as cytotoxic activities (Ingale and Hivrale 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Lectins are widely distributed in nature and found in all kinds of organisms such as plants, fungi, animals, bacteria, and viruses. [ 1 ] The amount of lectin varies in different organisms. In the plant kingdom, they are mainly seen in the seeds of leguminous plants.…”
Section: Introductionmentioning
confidence: 99%